THE EFFECT OF COMPETENCE AND MOTIVATION ON TEACHER PERFORMANCE WITH MODERATION OF ORGANIZATIONAL CULTURE: (Study on Madrasah Teachers In LP. Ma'arif NU In Gringsing District, Batang Regency) - Muarifudin, Muarifudin; Rijanti, Tristiana (International Journal of Social and Management Studies, 2022)
This study aims to determine the effect of competence and motivation on teacher performance by moderating organizational culture. Ma'arif NU throughout Gringsing District, Batang Regency. This research was conducted on 130 teachers of Madrasah Gringsing District, Batang Regency. The sample takes the entire population to be used as a research sample. Data analysis used validity test with component matrix, reliability test with Cronbach alpha, hypothesis was tested by multiple regression analysis.The results of the study found that competence had a positive effect on performance. Motivation has a positive effect on performance. Organizational culture is proven as a moderating variable both the effect of competence on performance and the effect of motivation on performance